2019
DOI: 10.3168/jds.2018-15648
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Search for superantigen genes in coagulase-negative staphylococci isolated from bovine milk in Canada

Abstract: The objective of the present study was to look for genes encoding for superantigens in bovine coagulasenegative staphylococci (CNS) isolated from milk in Canada. We screened by PCR 71 bovine CNS isolates, obtained from the Mastitis Pathogen Culture Collection managed by the Canadian Bovine Mastitis and Milk Quality Research Network (St-Hyacinthe, QC, Canada), for the presence of 13 superantigen genes. Our results indicate that these CNS isolates did not have any of the 13 superantigen genes screened for in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Most subclinical cases were associated with S. chromogenes (15.6%) followed by S. simulans (6.8%), S. xylosus (6.5%), S. haemolyticus (6.3%), S. cohnii (5.8%), S. epidermidis (5.5%), S. capitis (5.3%), S. sciuri (5.3%), S. gallinarum (5.0%), S. warneri (4.8%), S. equorum (4.5%), S. saprophyticus (4.0%), S. succinus (3.8%), S. arlettae (3.5%), and S. agnetis (3.3%). These findings are consistent with a growing number of studies which report that coagulase-negative staphylococci are emerging pathogens associated with mastitis and persistence of intramammary infection in bovine worldwide 7 . As observed in this study, in a recent Canadian study, the S. chromogenes and S. simulans were among the most common species found in clinical mastitis cases 8 .…”
Section: Discussionsupporting
confidence: 92%
“…Most subclinical cases were associated with S. chromogenes (15.6%) followed by S. simulans (6.8%), S. xylosus (6.5%), S. haemolyticus (6.3%), S. cohnii (5.8%), S. epidermidis (5.5%), S. capitis (5.3%), S. sciuri (5.3%), S. gallinarum (5.0%), S. warneri (4.8%), S. equorum (4.5%), S. saprophyticus (4.0%), S. succinus (3.8%), S. arlettae (3.5%), and S. agnetis (3.3%). These findings are consistent with a growing number of studies which report that coagulase-negative staphylococci are emerging pathogens associated with mastitis and persistence of intramammary infection in bovine worldwide 7 . As observed in this study, in a recent Canadian study, the S. chromogenes and S. simulans were among the most common species found in clinical mastitis cases 8 .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, only 5% of the 163 CNS bovine milk isolates were enterotoxin gene positive, with all 8 of the positive CNS strains harboring the seg gene only. The results of other studies, assaying different numbers and types of enterotoxin genes and applying different analytical methods, indicated that 0 to 80% of CNS strains tested were potentially enterotoxigenic (Nemati et al, 2008;Park et al, 2011;Fijałkowski et al, 2014;Bertelloni et al, 2015;Siqueira et al, 2017;Corbeil et al, 2019).…”
Section: Short Communicationmentioning
confidence: 99%
“…Screening 71 CNS bovine isolates for 12 enterotoxin genes (sea, seb, sec, sed, seg, selk, sell, selm, seln, selo, selp, selq) by single PCR (Corbeil et al, 2019) revealed the presence of 27 amplicons matching those typical for selo (9), sec (8), seg (5), seb (4), and sell (1) genes. However, when assessed by sequencing, none of these amplicons was confirmed as an enterotoxin gene.…”
Section: Short Communicationmentioning
confidence: 99%
“…Despite being considered minor mastitis pathogens [ 17 ], the importance of CoNS as a causative agent of intramammary infections in cattle is growing [ 18 ]. These may have coding genes for the biofilm formation, hemolysins, exoenzymes and superantigens [ 19 ], however, there is little information about their virulence factors [ 20 ] and the different immune response of the host to intramammary infections caused by environmental species or adapted to the host [ 18 ].…”
Section: Discussionmentioning
confidence: 99%